The Uses of Talent - Wolfle, Dael, 1906-2002 (Book collections on Project MUSE., 1971)
Looking at the uses and abuses of high-talent manpower in the United States, Dael Wolfle analyzes the ways in which this country produces, distributes, and utilizes its vital human resources. He examines changing trends in academic and professional supply and demand, and advocates long range administrative planning in order to avoid overspecialization and wasteful use of the professional labor force. To this discussion Dr. Wolfle brings twenty-five years' experience as a psychologist and student of the changing needs for and uses of high talent manpower. Basing his analysis on data from the d.